Effects of psilocybin, psychedelic mushroom extract and 5-hydroxytryptophan on brain immediate early gene expression: Interaction with serotonergic receptor modulators - Elad Lerer; Elad Lerer; Alexander Botvinnik; Orr Shahar; Meitar Grad; Meitar Grad; Karin Blakolmer; Noam Shomron; Noam Shomron; Amit Lotan; Bernard Lerer; Tzuri Lifschytz (Frontiers Media S.A., 2024)
Background: Immediate early genes (IEGs) are rapidly activated and initiate diverse cellular processes including neuroplasticity. We report the effect of psilocybin (PSIL), PSIL-containing psychedelic mushroom extract (PME) and 5-hydroxytryptophan (5-HTP) on expression of the IEGs, cfos, egr1, and egr2 in mouse somatosensory cortex (SSC).Methods: In our initial experiment, male C57Bl/6j mice were injected with PSIL 4.4 mg/kg or 5-HTP 200 mg/kg, alone or immediately preceded by serotonergic receptor modulators. IEG mRNA expression 1 hour later was determined by real time qPCR. In a replication study a group of mice treated with PME was added.Results: In our initial experiment, PSIL but not 5-HTP significantly increased expression of all three IEGs. No correlation was observed between the head twitch response (HTR) induced by PSIL and its effect on the IEGs. The serotonergic receptor modulators did not significantly alter PSIL-induced IEG expression, with the exception of the 5-HT2C antagonist (RS102221), which significantly enhanced PSIL-induced egr2 expression. 5-HTP did not affect IEG expression. In our replication experiment, PSIL and PME upregulated levels of egr1 and cfos while the upregulation of egr2 was not significant.Conclusions: We have shown that PSIL and PME but not 5-HTP (at a dose sufficient to induce HTR), induced a significant increase in cfos and egr1 expression in mouse SSC. Our findings suggest that egr1 and cfos expression may be associated with psychedelic effects.